PEMBERIAN DANA DESA KEPADA DESA ADAT DI BALI - Ni Putu Wilda Karismawati (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
There are two types of villages in government system of Bali Province, these are the OfficialVillage and the Customary Village. The Financial division of these two Villages in Bali isexpected to be regulated fairly because those two villages are recognized their existences,otherwise the provision of rural funding must also be given to these two villages. Nevertheless,the Regulation of Minister of Domestic Affairs No. 113 Year 2014 concerning on FinancialManagement does not regulate the usage of funds for the Customary Village.This study applied research of normative law that beganl. From the void norm in theprovision of rural funds to the Customary Villages in Bali. Thus, the result of this researchis the provision of rural funds to the Customary Village based on the Regulation of theMinister of Domestic Affairs No. 37 year 2007 concerning on Guidelines for Rural FinancialManagement and Regulation of Minister of Rural Affairs No. 5 year 2015 about Priority ofVillage Fund Usage year 2015. Meanwhile the responsibility is undertaken by the CustomaryVillage which the funds were transferred first to Village Revenues and ExpendituresBudget (APBDes) of Oficial Village, therefore the Customary Village are obliged to makeResponsibility Report (SPJ) in each use of funds.